Institutional quality and economic development in Algeria: An analytical study - Bokreta, Khadidja (International journal of economic perspectives, 2024)
Institutional quality plays a vital role in shaping the economic development of countries, particularly in advanced economies. This study examines the relationship between institutional quality and economic performance, with a focus on the institutional factors that either hinder or promote Algeria's economic development. Using both descriptive and analytical methods, the research explores the impact of inclusive versus extractive institutions on economic outcomes, emphasizing the importance of governance, law enforcement, and corruption control. The study highlights that Algeria faces significant institutional challenges, including inefficiencies in political and economic structures, which hinder development. The findings suggest that improving institutional quality, particularly through reforms that promote governance and judicial independence, could substantially enhance Algeria’s economic performance. Additionally, combating corruption by investing in human capital and strengthening educational institutions is essential for achieving sustained economic growth and diversification. The research underscores the need for comprehensive institutional reforms to support Algeria’s economic transformation and to ensure long-term prosperity.